THE TIME INDICATORS OF PERFORMANCE BY ORTHOPEDIC SPECIALISTS COMPLEX PROTOCOL OF MANUFACTURING COMPLETE CONDITIONALLY-REMOVABLE PROSTHESIS RELYING ON IMPLANTS - E.V. Diiev; V.A. Labunets; S.A. Schneider; T.V. Diieva (Ukrainian Medical Stomatological Academy, 2016)
Full conditionally removable dentures relying on dental implants are widely used in medical practice in Ukraine and are made either by injection basing on plastic burnout abutments, either by gluing basing on the abutment with the platform for bonding. Supports for such structures intraosseous implants are used in an amount of 2-6 units in the lower jaw and 4-8 units on upper one. Prosthesis is made both in immediate loading protocol, and in the protocol stitched in load time. In case, this type of denture still does not have, in our country, a full legal status for being applied. The purpose of research is to establish clinical and dental protocol runtime indicators for specialists manufacturing complete conditionally-removable prosthesis relying on implants. Materials and methods. Object of research - clinical and dental processes of orthopedic care for the manufacture of complete conditionally-removable denture relying on implants. Subject of research - the structure, sequence, duration and scope of the appropriate orthopedic care. Methods of research: to determine the structure and nature of labor costs of related professionals analytical method was used, to determine the duration of the relevant clinical and dental stages - timing method, to determine the amount of regulatory performance by prosthodontist and dental technician the mathematical processing of the results of the study were used, respectively, mathematical and statistical methods. Establishing methodological duration of the relevant phases of clinical and dental stages was used officially approved by the Ministry of Health of Ukraine. Methodology for establishing the duration of labor in dentistry been modified by V.A. Labunets (1999.) [14]. Results and discussion. Observing the work of 10 dentists-orthopedists and 10 dental technicians who produced for 10 patients a total of 15 full conditionally-removable dentures to support each of four implant has shown that the clinical protocol of their production includes 6 steps, while dental protocol consists of 5 laboratory stages. Normative duration indicators of these processes are determined according to the formula of establishing labor in prosthetic dentistry modified by Labunets V.A. (1999): НВ (attachment-stabilized overdenture) = (fixed costs working hours) (attachment-stabilized overdenture) + K (attachment-stabilized overdenture) × (variable costs working hours) (attachment-stabilized overdenture), where: HB (attachment-stabilized overdenture) oficial time of making conditionally removable prosthesis; (fixed costs working hours) (attachment-stabilized overdenture) - fixed costs of the expert time making conditionally removable prosthesis; (variable costs working hours) (attachment-stabilized overdenture) - variably-repeatable cost of professional time to the production of conditionally removable prosthesis; K (attachment-stabilized overdenture) - the number of conditionally-removable prosthesis, produced for a single patient. In the case of the identification of standard time for orthopedic dentists and dental technicians for the production of such kind of prosthetic for one patient the indicator is 2. After appropriate chronometry measurement and calculation of the main indicators of labor experts we have concluded: • The duration of the clinical protocol manufacturing by dentist-orthopedist for single patient one full conditionally-removable prosthesis relying on implants is 217,93 minutes. • The time required for the dental technician to manufacture a conditionally-removable denture meets the following criteria: the fixed costs of working time (fixed costs working hours) does not depend on the number of prostheses produced and their structure - 113,05 minutes, variably-repeatable cost of working time (variable costs working hours), which entirely depends on these factors - 129,34 minutes per one support in the prosthesis structure and 322,26 minutes in the entire coating of the denture.